PERBANDINGAN INTENSITAS CAHAYA BUATAN DAN ALAMI TERHADAP PERTUMBUHAN RUMPUT LAUT (Kappaphycus sp.) DI DALAM BAK TERKONTROL COMPARISON OF ARTIFICIAL AND NATURAL LIGHT INTENSITY ON THE GROWTH OF SEAWEED (Kappaphycus sp.) IN A CONTROLLED TUB - Amal Aqmal; Iswahyuddin Iswahyuddin; Andi Purwanti; St. Muriati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Light is the main determining factor in seaweed growth. Several research results show that each type of seaweed requires different light intensity. This research aims to determine the intensity of artificial and natural light on the growth of Kappaphycus sp seaweed. In this research, seaweed was maintained in fiber tubs measuring 3 x 2 x 1 m, with an initial weight of 100 g. The light sources used were 36 watt fluorescent lamps and sunlight. The treatments given were light intensity of 3000 lux, 6000 lux and sunlight. The results of this study show that the intensity of natural light (control) in the rainy season is still better than the use of artificial light (lamps) with an intensity of 3000 lux and 6000 lux for rearing seaweed seedlings in controlled tanks. Day-specific growth of seaweed Kappaphycus sp. The highest results were obtained in the treatment using natural light (outdoors) and absolute good growth was also obtained in the outdoor maintenance treatment.